Development and complex dynamics at school environment - Fuentes, Miguel Angel (2018)
In this work we use complex systems methodologies to analyze quantitatively the impact of an intervention involving cooperative and self-awareness activities on social interactions in children. The aim of this study is to evaluate behavioral plasticity of social relationships between peers in 6-7 year-olds who participated in the intervention conducted in a school context. The intervention consisted of 8 one-hour long sessions comprising mindfulness-based practices, collaborative activities that required cooperation, and perspective-taking instances in which children shared feelings, perceptions, and needs felt during the activities. We used complex network and game theory to evaluate pre-post-intervention variations. Social relationship was analyzed with a sociogram in both the intervention group and a control group which continued with regular classes. By means of the sociometric questionnaire we asked each child to mention which classmates he/she would choose as playmates and which he/she would not. Changes in the number of peers selected and rejected reflected changes in the pattern of social relationships pre-post-intervention. Our findings show that participating in the intervention positively modulated social interactions since we found an increase in the diversity and quality of positive links and a reduction in negative ones; a higher level of integration, indicated by enhanced positive networks where children with many positive connections tended to connect with those with few links; and more positive interactions between genders. These findings were not observed in the control group. Through the use of the mentioned methodologies, the current investigation provides new quantitative evidence of social network plasticity in children, an important topic which, to our knowledge, has been little studied. Results from this work indicate that positive transformations in social relationships can be fostered through the performance of this kind of intervention.